Escola bilíngue para surdos : constituição de práticas que configuram um espaço bilíngue - Drumond, Andréa Hees (2017)
It is a matter of problematizing inclusive education in the bilingual proposal for the deaf. The objective is based on the tensions that arise between bilingual practices and the policies that constitute them, focusing not only on the role of the educator, the interpreter, the instructor, but also the deaf student in the school context.The research proposal is to make considerations about what has been done in practical terms, as well as what is intended in the context of public policies and in the records of school practices in a bilingual municipal school. On this process, were analyzed the following documents Declaration of Salamanca (1994); The education that we, the deaf, want (1999); the decree 5626 from December 22th of 2005 that regulates the law 10.436 April 24th of 2002 which dispossess about Brazilian sign language and others. From the theorizations of Michael Foucault, and authors that discuss with him, tries to develop a reflection based on genealogical analysis looking pass to understand aspects from the present, using tool concepts as notions of “governing” and “in/exclusion” to analyze the data produced. In this sense, the deafness is understood situated by the cultural bias and the bilingual education as a pedagogical proposition that considers the linguistic condition and cultural of deaf student. The paper investigate those practices through a qualitative research and principles of a descriptive-exploratory ethnographic study. For data collection, instruments such as observation in the classroom, open questionnaires, classroom activities, and the perception of practices that facilitate the inclusion of deaf students in a bilingual proposal are used. Data analysis shows that the ideological disputes between the deaf and the hearing have been influencing the language policies in the area of deafness, and it is necessary to reflect on the mechanisms of control possibly exercised over these subjects, in order to govern identity and deaf difference, as well as How the deaf are subjected and led to productive participation in the contemporary world through the Sign Language, deaf culture and bilingual training.